2015
DOI: 10.1007/s00415-014-7623-1
|View full text |Cite
|
Sign up to set email alerts
|

Early diagnosis of cardiac involvement in idiopathic inflammatory myopathy by cardiac magnetic resonance tomography

Abstract: The aim of this study was to investigate cardiac involvement in patients with idiopathic inflammatory myopathies excluding inclusion body myositis with cardiac magnetic resonance tomography (CMR). A case series of 53 patients with polymyositis, dermatomyositis, or non-specific myositis underwent CMR including functional imaging, T1-weighted, and late gadolinium enhancement (LGE) imaging. T1-weighted and LGE images were analyzed for myocardial enhancement. Reduced left ventricular function (LVF) was found in 9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
51
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 26 publications
5
51
0
1
Order By: Relevance
“…The LGE technique at cardiac MRI is an accurate method to detect focal fibrosis with gadolinium‐based contrast agents and has proven to have significant prognostic implications in nonischemic cardiomyopathies . In our study, the LGE pattern localized in the midwall and/or the subepicardial layer, which was similar to previous reports as well as other autoimmune diseases . The incidence of LGE in our PM/DM cohort was 19%, with all patients having a nonischemic‐pattern of LGE, which was lower than previous studies showing the prevalence of LGE in 56.3–62.2% patients .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The LGE technique at cardiac MRI is an accurate method to detect focal fibrosis with gadolinium‐based contrast agents and has proven to have significant prognostic implications in nonischemic cardiomyopathies . In our study, the LGE pattern localized in the midwall and/or the subepicardial layer, which was similar to previous reports as well as other autoimmune diseases . The incidence of LGE in our PM/DM cohort was 19%, with all patients having a nonischemic‐pattern of LGE, which was lower than previous studies showing the prevalence of LGE in 56.3–62.2% patients .…”
Section: Discussionsupporting
confidence: 86%
“…Cardiac magnetic resonance imaging (MRI) is a valuable noninvasive imaging modality for evaluation of myocardial inflammation in myocarditis and in assessment of myocardial involvement in autoimmune disease . Recent uncontrolled data showed a high proportion (56–62%) of IIM patients presenting with late gadolinium enhancement (LGE), indicating focal fibrosis . However, the detection of LGE depended on the comparison of damaged myocardium against distant “normal” myocardium, which is a suboptimal technique for detecting diffuse myocardial fibrosis.…”
mentioning
confidence: 99%
“…Clinical manifestations of cardiac involvement in IIM patients can range from none to arrhythmia, heart failure, and even cardiac death [5]. Previous studies have found cardiac involvement manifesting as diastolic dysfunction or decreased longitudinal strain by echocardiography [6,7], abnormalities on electrocardiography (ECG) [6], presence of myocardial late gadolinium enhancement (LGE) [3,8,9], increased myocardial T1and T2 values [10][11][12], and increased extracellular volume (ECV) [13] by cardiovascular magnetic resonance (CMR). Although a few previous studies have reported the potential value of multiparametric CMR techniques in identifying cardiac involvement in patients with IIM [10,11], there is still a lack of dynamic monitoring of myocardial histological changes during therapy.…”
mentioning
confidence: 99%
“…Heart involvement in idiopathic inflammatory myopathies was also detected by cardiac magnetic resonance tomography [5] or echocardiography [6], and these findings may lead to therapeutic treatment for the cause of morbidity [7]. An increased risk of myocardial infarction or conduction abnormalities was reported in patients with idiopathic inflammatory myopathies [8].…”
Section: Introductionmentioning
confidence: 99%
“…An increased risk of myocardial infarction or conduction abnormalities was reported in patients with idiopathic inflammatory myopathies [8]. Moreover, left ventricular diastolic dysfunction [6] and reduced left ventricular ejection fractions (EF) [5] were observed in patients regardless of the presence of myalgia, paresis, and exhaustion. Few studies have demonstrated the relationship between cardiac functions and exercise capacity in patients with idiopathic inflammatory myopathies.…”
Section: Introductionmentioning
confidence: 99%